4-Amino-3-pentadecyl-3H-1, 2, 4-triazole-3-thiones and 3-pentadecyl-1, 3, 4-oxadiazole-2(3H)-thione for the preparation of dimeric palladium(II) complexes and their applications in Tsuji–Trost and Mizoroki–Heck reactions. Issue 10 (19th May 2019) - Chehrouri, Manel; Othman, Adil A.; Jiménez-Cecilia, Samuel; Moreno-Cabrerizo, Cristina; Sansano, José M.
Abstract: The synthesis of palladium complexes derived from 4-amino-3-pentadecyl-3 H -1, 2, 4-triazole-3-thiones and 3-pentadecyl-1, 3, 4-oxadiazole-2(3 H )-thiones are reported. They were obtained from palladium acetate and dipotassium tetrachloropalladate(II) and their composition was assigned by elemental analysis (solid state). The resulting metallic entities were also characterized in solution based in mass spectrometry experiments. Their application in organic synthesis as cross-coupling reaction catalysts is described. One example of both conventional Tsuji–Trost and Mizoroki–Heck reactions were efficiently carried out in very high chemical yield. GRAPHICAL ABSTRACT: